Da escola de ofício a profissão educação física: a constituição do habitus profissional de professor - Neto, Samuel de Souza [UNESP]; Benites, Larissa Cerignoni [UNESP]; Gomes da Silva, Mellissa Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2010)
Study addresses the question of elements that constitute the habitus of professional teacher, and the construction of teacher identity the starting point. As a result it was concluded that the professional habitus consists of a grammar-generating practices, routines and schemes involving didactic actions, hexis body and posture.

Este estudo trata da questão dos elementos que constituem o habitus profissional de professor, tendo na construção da identidade docente o ponto de partida. Como resultado concluiu-se que o habitus profissional é formado por uma gramática geradora de práticas, rotinas e esquemas que envolvem ações didáticas, hexis corporal e postura.
School of craft the profession of physical education: the constituition of the professional teacher habitus
Keywords: Physical Education; Habitus; Profession